Proteomic study of the inhibitory effects of tannic acid on MRSA biofilm - Miao, Yang; Shuang, Wang; Qianwei, Qu; Xin, Liu; Wei, Peng; Hai, Yang; Yonghui, Zhou; Xinbo, Yu (Frontiers in Pharmacology, 2024)
Introduction The mechanism of tannic acid (TA) intervention on methicillin-resistant Staphylococcus aureus (MRSA, USA 300) biofilm formation was explored using proteomics. Methods The minimum inhibitory concentration (MIC) of TA against the MRSA standard strain USA 300 was determined by two-fold serial dilution of the microbroth. The effects of TA were studied using crystal violet staining. The morphology of TA-treated USA 300 cells was observed by scanning electron microscopy and confocal laser scanning microscopy. Differentially expressed proteins (DEPs) were screened using proteomic and biological information analyses, and their transcriptional levels were verified using real-time quantitative polymerase chain reaction. Results The MIC of TA was 0.625 mg/mL, whereas 1/2 MIC (0.3125 mg/mL) of TA significantly inhibited biofilm formation without affecting the bacterial growth (p < 0.01) and prevented the formation of a complete three-dimensional biofilm structure. Using 1/2 MIC of TA, 208 DEPs were identified, of which 127 were upregulated and 81 were downregulated. The transcriptional levels of the genes corresponding to five randomly selected DEPs (glnA, ribD, clpB, gap, and lukE) were consistent with the proteomics data (p < 0.05). Bioinformatic analysis showed that the changes in the MRSA strains after TA intervention primarily involved pyrimidine and purine metabolisms, arginine biosynthesis, and the citric acid cycle. Conclusion TA exerts an antibacterial effect on MRSA and can be used as a potential candidate for the development of anti-biofilm drugs, thereby laying a foundation for the treatment of MRSA biofilm-induced infections.